Metabolic modulation of chromatin: implications for DNA repair and genomic integrity - Liu, Jinping; Kim, Jeongkyu; Oberdoerffer, Philipp (Frontiers in Genetics, 2013)
The maintenance of genomic integrity in response to DNA damage is tightly linked to controlled changes in the damage-proximal chromatin environment. Many of the chromatin modifying enzymes involved in DNA repair depend on metabolic intermediates as cofactors, suggesting that changes in cellular metabolism can have direct consequences for repair efficiency and ultimately, genome stability. Here, we discuss how metabolites may contribute to DNA double-strand break repair, and how alterations in cellular metabolism associated with both aging and tumorigenesis may affect the integrity of our genomes.